2018
DOI: 10.1111/tpj.13902
|View full text |Cite|
|
Sign up to set email alerts
|

Shoot phytochrome B modulates reactive oxygen species homeostasis in roots via abscisic acid signaling in Arabidopsis

Abstract: Underground roots normally reside in darkness. However, they are often exposed to ambient light that penetrates through cracks in the soil layers which can occur due to wind, heavy rain or temperature extremes. In response to light exposure, roots produce reactive oxygen species (ROS) which promote root growth. It is known that ROS-induced growth promotion facilitates rapid escape of the roots from non-natural light. Meanwhile, long-term exposure of the roots to light elicits a ROS burst, which causes oxidativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…It is known that ABA treatment increases ROS accumulation in plants (Bohmer and Schroeder, ; Ha et al , ). Our results, however, showed that ABA decreased ROS accumulation in salt‐treated hss mutant.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that ABA treatment increases ROS accumulation in plants (Bohmer and Schroeder, ; Ha et al , ). Our results, however, showed that ABA decreased ROS accumulation in salt‐treated hss mutant.…”
Section: Discussionmentioning
confidence: 99%
“…1 Our recent findings indicate that shoot phyB promotes ABA synthesis in the shoot, and the shoot-derived ABA itself or signals induces root elongation by detoxifying ROS. 10 Consistent with this notion, ROS accumulate in the roots of phyb mutant that exhibits reduced primary root growth upon exposure to long-term light illumination. This entails that shoot ABA itself or as-yet unknown ABA signaling molecule links the shoot phyB-sensed light perception and ROS homeostasis in the underground roots.…”
Section: Textmentioning
confidence: 68%
“…We have previously demonstrated that phyB mediates ABA biosynthesis in the shoots and ABA triggers the expression of PEROXIDASE1 gene by stabilization ABA INSENSITIVE5 transcription factor. 10 Considering the importance of the synchronization and communication between the shoot and root parts, more works are required for further understanding root photomorphogenesis.…”
Section: Textmentioning
confidence: 99%
“…It is shown that light regulates the whole process of root formation [12][13][14]. Some factors such as reactive oxygen species, abscisic acid, sugar and auxin, which is involved in light signal pathway are found to affect root development [15][16][17]. IAA is synthesized in vigorous organ under light regulation [18][19], and IAA synthesis depended on light play an criticle role on developmental process of adventitious roots including induction, development and expression of root [20,21].…”
mentioning
confidence: 99%